Radiographic Quality of Root Canal Obturation Performed By Fifth Year Students of Hamadan Dental School - Eskandarloo, Amir; Karkehabadi, Hamed; Hoseini Hashemi, Seyedeh Zeinab; Ahmadi, Masoumeh; Hendi, Seyedeh Sareh (Iranian Endodontic Journal, 2017)
Introduction: The aim of this study was to assess the radiographic technical quality of root canal therapy performed by fifth year students of Dental School of Hamadan University of Medical Sciences from 2015 to 2016. Methods and Materials: Four hundred and seventy records of root canal therapies were evaluated. Records with graphies taken as initial, master apical file (MAF), master apical cone (MAC) and final radiographs were included in the study and records of patient younger than 16 years and older than 68 years were excluded from further investigations. Lastly, 432 teeth were selected. Obturation length, canal tapering, quality and density of filling material were the variables investigated in the present study. Two independent investigators examined the radiographies using a magnifying lens (×2) and x-ray viewer. Data were analyzed using chi-square test. Results: The technical quality of root filling performed by undergraduate dental students was classified as acceptable in 10.4% of cases. Moreover, 70.8% of teeth had adequate filling, 17.1% were underfilled and 12% were overfilled. The three groups were significantly different in terms of working length and taper quality. One hundred ninety four (44.9%) records had adequate taper and 109 (25%) records had adequate density. There was a significant association between teeth location and the length of obturation so that the probability of a successful treatment was higher in maxillary teeth. Furthermore, the rate of a proper length of obturation was higher among incisors than that of premolars and molars. Conclusion: The technical quality of root canal therapy performed by dental students in Hamadan University of medical sciences is not as acceptable as it should be. One of the most important factors in this regard is a high student/professor ratio. Keywords: Dental Students; Quality Control; Root Canal Obturation; Root Canal Therapy